THE EFFECTIVENESS OF THE STARSTREAK MISSILE DEFENSE SYSTEM PREPARATION STRATEGY IN SUPPORTING THE INDONESIAN ARMY'S MAIN TASKS (STUDY AT THE 14TH AIR DEFENSE BATTALION/PWY): EFEKTIVITAS STRATEGI PENYIAPAN ALUTSISTARUDAL STARSTREAK DALAM MENDUKUNG TUGAS POKOK TNI AD (STUDI DI YONARHANUD 14/PWY) - Pujo Andriana; Guntur Eko Saputro; Edy Saptono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to identify and analyze the readiness condition of the Starstreak Missile Alutsista (Main Weaponry System) at Yonarhanud 14/PWY (Air Defense Artillery Battalion 14/PWY), formulate strategies to improve its readiness, and develop a framework to measure the effectiveness of the implementation of these strategies. A qualitative research method with a case study approach was used. The research results indicate that the current readiness condition of the Starstreak Missile Alutsista is not yet optimal. Several influencing factors include: 1) Unfulfilled number of Alutsista; 2) Limited number and competence of technicians; 3) Limited facilities and infrastructure; 4) Inadequate budget support; and 5) Dependence on external parties. The proposed strategies include improving personnel, facilities and infrastructure, budget support, self-maintenance capabilities, and coordination.